Psychological assistance for military personnel as a social institute - Kozhedub, Olena; Klimishyna, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . Today, modern Ukrainian society is witnessing transformational processes that are characteristic of many spheres of life and that require theoretical and methodological substantiation of both the ways of such social changes and the mechanisms of their implementation. And in this regard, the most adequate is the institutional theory. The full-scale invasion of Russia on the territory of Ukraine actualized the problem of organizing professional psychological assistance to military personnel. The purpose of the study is to reveal the institutional nature of psychological assistance to military personnel.M e t h o d s . The research used general scientific methods – analysis, synthesis, generalization.R e s u l t s . Implementing an institutional approach, in the study of psychological assistance, researchers analyze the structural components of the institution of psychological assistance. In the course of the research, it was determined that these components are: documented social norms and rules that determine the specifics of providing psychological assistance to military personnel; special institutions, organizations that provide psychological assistance to military personnel (combat stress control groups and psychological support and recovery groups); a specialized subject – a psychologist who works directly with those military personnel who need psychological help; a system of sanctions, the purpose of which is to exercise social control over the activities of the Institute of Psychological Assistance to Military Personnel. The article discusses such types of psychological help as psychoprophylaxis, psychological counseling, psychocorrection and psychotherapy.C o n c l u s i o n s . An institutional approach was applied in the analysis of the system of psychological assistance to military personnel. The components of the Institute of Psychological Assistance are briefly described and the types of psychological assistance to military personnel are described.
Keywords: institutionalization, social institution, structure of social institution, institutionalization of psychological assistance to military personnel